ANALYSIS OF SHORT STORY “THE TELL-TALE HEART” BY EDGAR ALLAN POE: INDICATIONS FOR STYLISTICS TEACHING. - Arif Firmansyah (Cahaya Ilmu Bangsa Institute, 2024)
This essay uses style analysis as a tool to examine the narrator's internal and external worlds in the short story